Pengaruh inflasi, suku bunga, investasi terhadap pertumbuhan ekonomi Provinsi Jambi - Risky Nofitasari; Amri Amir; Candra Mustika (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2017)
This study aims to analyze: 1) the inflation trend, interest rates, investment and economic growth of Jambi Province; 2) the influence of inflation, interest rates, investment on economic growth in Jambi Province. The data used are secondary data time series during the period 2000 - 2016. Data is sourced from the Jambi Provincial Statistics Agency and Bank Indonesia. Data analysis was carried out descriptively and multiple regression models. The results of the study found: 1) the average inflation in Jambi Province was 7.64 percent per year, credit interest rates were 13.67 percent per year, investment development was 15.33 percent per year, and economic growth was 5.45 percent per year; 2) Simultaneously, inflation, lending and investment interest rates have a significant effect on economic growth in Jambi Province. Partially, credit interest rates have a significant negative effect and investment has a significant positive effect on economic growth in Jambi Province. Conversely inflation does not have a significant effect.